Understanding the uptake of virtual care for first and return outpatient appointments in child and adolescent mental health services: a mixed-methods study - Leslie Anne Campbell; Sharon E Clark; Jill Chorney; Debbie Emberly; NJ Carrey; Alexa Bagnell; Jaime Blenus; Miriam Daneff; John Charles Campbell (BMJ Open)
Objective To describe patterns of virtual and in-person outpatient mental health service use and factors that may influence the choice of modality in a child and adolescent service.Design A pragmatic mixed-methods approach using routinely collected administrative data between 1 April 2020 and 31 March 2022 and semi-structured interviews with clients, caregivers, clinicians and staff. Interview data were coded according to the Consolidated Framework for Implementation Research (CFIR) and examined for patterns of similarity or divergence across data sources, respondents or other relevant characteristics.Setting Child and adolescent outpatient mental health service, Nova Scotia, Canada.Participants IWK Health clinicians and staff who had participated in virtual mental healthcare following its implementation in March 2020 and clients (aged 12–18 years) and caregivers of clients (aged 3–18 years) who had received treatment from an IWK outpatient clinic between 1 April 2020 and 31 March 2022 (n=1300). Participants (n=48) in semi-structured interviews included nine clients aged 13–18 years (mean 15.7 years), 10 caregivers of clients aged 5–17 years (mean 12.7 years), eight Community Mental Health and Addictions booking and registration or administrative staff and 21 clinicians.Results During peak pandemic activity, upwards of 90% of visits (first or return) were conducted virtually. Between waves, return appointments were more likely to be virtual than first appointments. Interview participants (n=48) reported facilitators and barriers to virtual care within the CFIR domains of ‘outer setting’ (eg, external policies, client needs and resources), ‘inner setting’ (eg, communications within the service), ‘individual characteristics’ (eg, personal attributes, knowledge and beliefs about virtual care) and ‘intervention characteristics’ (eg, relative advantage of virtual or in-person care).Conclusions Shared decision-making regarding treatment modality (virtual vs in-person) requires consideration of client, caregiver, clinician, appointment, health system and public health factors across episodes of care to ensure accessible, safe and high-quality mental healthcare.